Tinjauan Historis-Deskriptif tentang Sejarah Kodifikasi dan Pelestarian Al-Qur’an pada Masa Nabi Muhammad SAW hingga Era Khulafaur Rasyidin - Anggita Maghfirotul Ismanudin; Carisa Septianti Dwi Novita; Aulia Rohmataz Zubaidah; Abdurrahman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This article examines the process of Qur’anic codification and preservation from the time of Prophet Muhammad (peace be upon him) to the era of the Khulafā’ al-Rāsyidīn, addressing the limited systematic studies that view codification as a unified historical and scientific process. The study aims to identify the stages of Qur’anic codification, the verification mechanisms employed by early Muslim communities, and their epistemological significance in shaping Islamic scholarly tradition. Using a qualitative library research method with historical and epistemological approaches, data were collected from classical works on ʿUlūm al-Qur’ān, historical sources related to Qur’anic compilation, and recent academic publications. Data were analyzed through content analysis. The findings show that Qur’anic preservation was carried out through a layered verification system combining collective memorization and authenticated written records. The codification under Abū Bakr al-Ṣiddīq and the standardization of the muṣḥaf during the caliphate of ʿUthmān ibn ʿAffān represent early scientific practices aimed at safeguarding the authority of the Qur’anic text. This study positions Qur’anic codification as an epistemological foundation for the development of Islamic sciences and as an early model of knowledge preservation in the Islamic tradition